1996
DOI: 10.1073/pnas.93.18.9827
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 fimbrial expression enhances Escherichia coli virulence for the urinary tract.

Abstract: Type 1 fimbriae are adhesion organelles expressed by many Gram-negative bacteria. They facilitate adherence to mucosal surfaces and inflammatory cells in vitro, but their contribution to virulence has not been defined. This study presents evidence that type 1 fimbriae increase the virulence ofEscherichia coli for the urinary tract by promoting bacterial persistence and enhancing the inflammatory response to infection. In a clinical study, we observed that disease severity was greater in children infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
536
2
11

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(560 citation statements)
references
References 44 publications
11
536
2
11
Order By: Relevance
“…Type 1-mediated adherence has been proposed to play a role in the induction of inflammation, enhancing E. coli virulence for the urinary tract. CONNELL et al, (1996) 4 reported that mice infected with a type 1-positive 01:K1:H7 isolate showed a higher urinary neutrophil influx into the urine than type 1-negative isolates. Furthermore, we demonstrated that 76 fimH strains, occurred with at least one adhesin, such as pap, sfa, or afa.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1-mediated adherence has been proposed to play a role in the induction of inflammation, enhancing E. coli virulence for the urinary tract. CONNELL et al, (1996) 4 reported that mice infected with a type 1-positive 01:K1:H7 isolate showed a higher urinary neutrophil influx into the urine than type 1-negative isolates. Furthermore, we demonstrated that 76 fimH strains, occurred with at least one adhesin, such as pap, sfa, or afa.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 fimbriae bind to mannosylated glycoproteins rather than glycosphingolipids and have been shown to adhere efficiently to the murine uro-epithelium and to activate the innate host response in the murine urinary tract [21]. Experimental UTI was established in C57BL/6 Tlr4 WT/ WT or Tlr4 -/-mice with E. coli S1918 fim + or the fimvector control (Fig.…”
Section: Type 1 Fimbriated E Coli Involve Tlr4 and Myd88mentioning
confidence: 99%
“…The host cell receptors for P are glycosphingolipids, and the PapG tip adhesin binds to oligosaccharide receptor epitopes, which are abundantly expressed in the human urinary tract mucosa [19,20]. Type 1 fimbriae differ in receptor specificity, as they recognise mannosylated glycoproteins rather than glycosphingolipids, but both P and type 1 fimbriae trigger the innate host response in the murine urinary tract [21][22][23][24]. In addition, P fimbriae are sufficient to stimulate the innate host response in the human urinary tract and thus fulfil the molecular Koch postulates as independent virulence factors in vivo [25,26].…”
mentioning
confidence: 99%
“…The expression and binding of these various adhesins to epithelial cell receptors determine tissue specificity and allow UPEC isolates to ascend to the lower urinary tract and the kidney in experimental models of UTI (3)(4)(5)(6)(7)(8).…”
Section: Renal Collecting Duct Epithelial Cells React Tomentioning
confidence: 99%